(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article examines the problem of literary genre and its transformation in contemporary literature. It argues that traditional generic boundaries have become increasingly fluid under the influence of postmodernism, digital technologies, and globalization. Through the analysis of hybrid forms such as autofiction, graphic novels, fanfiction, and digital literature, the study demonstrates how the concept of genre is being redefined in the 21st century. The paper concludes that the genre remains a relevant but dynamic category that reflects cultural, social, and technological changes in the literary field.